Ćwiczenie czytania w języku obcym wspomagane komputerowo programem Colorado Literacy Tutor - Juszczyk, Konrad (Investigationes Linguisticae, 2006)
Successful tutorship of reading depends on several conditions. Teaching to read require well prepared method with scientific foundations. Children expect entertaining exercises supported with motivational system and a patient tutor who helps in perfecting the skills related to reading. At last, the whole tutorship should be scalable, so large groups of children and whole schools can learn to read step by step. Their progress should be observable for teachers, parents and researchers. Computer assisted reading tutoring may fulfill all these conditions. Colorado Literacy Tutor is a program especially designed to meet these expectations and this article is to explore its possibilities. Short report on pioneer testing of CLT on Polish children is also given.